Dictionary of scientific biography. [Volumes 7 & 8] - Gillispie, Charles Coulston; American Council of Learned Societies (London : Simon & Schuster and Prentice Hall International, 1981)
Contains articles that provide information about the professional lives of scientists, from classical antiquity to modern times, who have made significant contributions to the fields of mathematics, astronomy, physics, chemistry, biology, and earth science. Arranged alphabetically from Iamblichus to Macquer.
v. 7. Iamblichus-Karl Landsteiner -- v. 8. Jonathan Homer Lane-Pierre Joseph Macquer.
"Published under the auspices of the American Council of Learned Societies"--P. facing t.p.
Includes bibliographical references.
Wilson's Senior High School.
Young Adult
Keywords: Scientists -- Biography -- Dictionaries; Scientists -- Biography -- Dictionaries